Effect of Polymer Concentration on the Morphology and Mechanical Properties of Asymmetric Polysulfone (PSf) Membrane (Journal of Applied Membrane Science & Technology, 2017)
Polymer concentration had been identified as one of the important parameters tailoring the membrane properties. In this work, the effects of polymer concentration on the morphological and mechanical properties of membrane were investigated at three different polymer concentrations, i.e., 20, 25 and 30 wt%. The viscosity of dope solutions were determined to estimate the optimum polymer concentration.Â  The morphological properties of the fabricated membrane were determined using SEM whereas the mechanical properties of the membrane were investigated using tensile tester. Results show that an increase in the polymer concentration could lead to the improvement of the morphological and mechanical properties of the membrane. The tensile strength of the membrane determined for PSf-20, PSf-25 and PSf-30 are 5.73, 6.59 and 7.03 MPa, respectively whereas the elongation at break measured for the membranes are 46.99%, 69.18% and 36.27%, respectively. As shown in this work, the polymer concentration played a significant role to alter on membrane morphology and mechanical strength.Â